Endovascular Revascularization Plus Supervised Exercise Versus Supervised Exercise Only for Intermittent Claudication: A Cost-Effectiveness Analysis. (13th July 2021) - Fakhry, Farzin; Rouwet, Ellen V.; Spillenaar Bilgen, Reinier; van der Laan, Lijckle; Wever, Jan J.; Teijink, Joep A.W.; Hoffmann, Wolter H.; van Petersen, Andre; van Brussel, Jerome P.; Stultiens, Guido N.M.; Derom, Alex; den Hoed, P. Ted; et al.
Abstract : Background: The ERASE (Endovascular Revascularization and Supervised Exercise) study showed that a combination therapy of endovascular revascularization followed by supervised exercise resulted in greater improvement in walking ability and quality of life as compared with supervised exercise only (standard care) in patients with intermittent claudication. The cost-effectiveness of the combination therapy as compared with supervised exercise is not well defined. In this report, the cost-effectiveness analysis of the ERASE study is presented. Methods: Two hundred twelve patients were randomly assigned to the combination therapy (n=106) or supervised exercise only (n=106) and were followed for 12 months. Cumulative costs per patient were collected using the in-hospital resource utilization data and cost-questionnaires. Quality-adjusted life years were estimated using the EuroQol-5D questionnaire. Incremental cost-effectiveness ratios were calculated from both the health care and societal perspective. The associated uncertainty was determined using bootstrap techniques and acceptability curves. Results: As compared with supervised exercise only, the combination therapy cost an additional €1.462 (99% CI, 388 to 3862) from the health care perspective and €161 (99% CI, −2286 to 3106) from the societal perspective. Accumulated quality-adjusted life- years during 1 year follow-up were 0.042 (99% CI, −0.009 to 0.118) higher in the combination therapy group. The incremental cost-effectiveness ratio was €34.810 from the health care perspective and €3.833 from the societal perspective. Compared with supervised exercise, at a willingness-to-pay threshold of €80.000 per quality-adjusted life-year, the combination therapy had a probability of 87% and 95% of being cost-effective from the health care and societal perspective, respectively. Conclusions: Combination therapy of endovascular revascularization followed by supervised exercise is clinically and economically a more attractive approach than supervised exercise only for intermittent claudication up to 12-month follow-up. Yet, the long-term cost- and clinical effectiveness of both strategies for specific patient groups remains to be defined. Registration: URL: https://www.trialregister.nl ; Unique identifier: NTR2249.